2008
DOI: 10.1098/rspb.2008.0062
|View full text |Cite
|
Sign up to set email alerts
|

Function of bright coloration in the wasp spider Argiope bruennichi (Araneae: Araneidae)

Abstract: There are two major competing explanations for the counter-intuitive presence of bright coloration in certain orb-web spiders. Bright coloration could lure insect prey to the web vicinity, increasing the spider's foraging success. Alternatively, the markings could function as disruptive camouflage, making it difficult for the insect prey to distinguish spiders from background colour variation. We measured the prey capture rates of wasp spiders, Argiope bruennichi, that were blacked out, shielded from view usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 33 publications
2
39
1
Order By: Relevance
“…Lately, there has been increased interest in the potential impacts of predators on pollination services and plant fitness (Suttle 2003 (Heiling et al 2006;Bush et al 2008), to lure their prey. Crab spiders (Thomisidae), which are sit-and-wait predators that ambush pollinators on flowers, are perhaps the best studied of these predators (Dukas & Morse 2003;Reader et al 2006;Gonçalves-Souza et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Lately, there has been increased interest in the potential impacts of predators on pollination services and plant fitness (Suttle 2003 (Heiling et al 2006;Bush et al 2008), to lure their prey. Crab spiders (Thomisidae), which are sit-and-wait predators that ambush pollinators on flowers, are perhaps the best studied of these predators (Dukas & Morse 2003;Reader et al 2006;Gonçalves-Souza et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, although Argiope spiders with linear decorations may have lower foraging success, this could be buffered by the attractive properties of their bright body coloration. Recent studies showed that bright coloration of various taxa of orb-web spiders, including Argiope, in itself is attractive to insects (Craig and Ebert, 1994;Hauber, 2002;Tso et al, 2002;Tso et al, 2004;Tso et al, 2006;Cheng and Tso, 2007;Bush et al, 2008). We suggest that the evolution of spider web decorations was shaped by a complex array of interacted selection pressures (such as foraging performance vs predation pressure) and might have co-evolved with other traits (such as body coloration).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the colorful orbweaving spiders (Nephila pilipes) in Taiwan also have been reported to catch significantly more prey than its melanic conspecific (Tso et al, 2002;Tso et al, 2004). In addition, several diurnal as well as nocturnal species of spiders have been demonstrated to significantly reduce their foraging success if their color markings were experimentally altered (Bush et al, 2008;Chuang et al, 2007;Chuang et al, 2008;Hauber, 2002;Tso et al, 2007;Tso et al, 2002;Tso et al, 2006). All this evidence indicates that the conspicuous body coloration in spiders is to lure their prey (see Vanderhoff et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…However, recent behavioral experiments in orbweaving spiders (N. pilipes), orchid spiders (Leucauge magnifica), nocturnal orb spiders (Neoscona punctigera) and wasp spiders (Argiope bruennichi) showed that the prey capture rate was significantly lower if the color markings were blocked or if the spider was removed from the web (Bush et al, 2008;Chuang et al, 2007;Chuang et al, 2008;Tso et al, 2006). Thus, it is most likely that the bright body colorations of these spiders function as visual lures to attract insects, although some opposite evidences exist (Hoese et al, 2006;Václav and Prokop, 2006).…”
Section: Does the Orb-weaving Spider 'Aggressively Mimic' A Flower?mentioning
confidence: 99%